2021
DOI: 10.1007/s00603-021-02474-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Deformation of Opalinus Clay at Elevated Temperature and Pressure Conditions: Mechanical Properties and the Influence of Rock Fabric

Abstract: The mechanical behavior of the sandy facies of Opalinus Clay (OPA) was investigated in 42 triaxial tests performed on dry samples at unconsolidated, undrained conditions at confining pressures (pc) of 50–100 MPa, temperatures (T) between 25 and 200 °C and strain rates ($$\dot{\varepsilon }$$ ε ˙ ) of 1 × 10–3–5 × 10–6 s−1. Using a Paterson-type deformation apparatus, samples oriented at 0°, 45° and 90° to bedding were deformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 131 publications
2
20
0
Order By: Relevance
“…A consolidation coefficient of 0.002 mm 2 /s is reported in Schuster et al (2021), which is broadly in line with measurements on Opalinus Clay obtained in oedometric or triaxial conditions in other works (Crisci et al 2019;Ferrari et al 2016;Minardi et al 2019). Computing the strain rate for drained and undrained shearing (Head and Epps 2014), values in the order of magnitude 10 -8 1/s and 10 -7 1/s would be obtained, respectively.…”
Section: Strain Ratesupporting
confidence: 87%
See 4 more Smart Citations
“…A consolidation coefficient of 0.002 mm 2 /s is reported in Schuster et al (2021), which is broadly in line with measurements on Opalinus Clay obtained in oedometric or triaxial conditions in other works (Crisci et al 2019;Ferrari et al 2016;Minardi et al 2019). Computing the strain rate for drained and undrained shearing (Head and Epps 2014), values in the order of magnitude 10 -8 1/s and 10 -7 1/s would be obtained, respectively.…”
Section: Strain Ratesupporting
confidence: 87%
“…higher mean effective stress, with respect to S-samples. In Schuster et al (2021), while comparing the results between P-and S-samples in terms of total confining stress, the two seem to show a remarkable difference in terms of peak strength, while the discrepancy is reduced when effective stress is considered. Data from Minardi et al (2020) showed that the failure envelope for P-samples had an intercept about 70% higher than the S-samples, while the shear strength angle remains substantially unchanged.…”
Section: Pore Pressure Generationmentioning
confidence: 90%
See 3 more Smart Citations